2002
DOI: 10.1007/s00213-002-1045-y
|View full text |Cite
|
Sign up to set email alerts
|

Chronic citicoline increases phosphodiesters in the brains of healthy older subjects: an in vivo phosphorus magnetic resonance spectroscopy study

Abstract: The increases in phosphodiesters seen in this study indicate that phospholipid synthesis and turnover were stimulated by 6 weeks of oral citicoline. These results in humans support previous in vitro and animal studies and suggest that the administration of oral citicoline may be of use in reversing age-related changes in the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…Results from this study are consistent with prior research that suggests citicoline may play a role in increasing attention and alertness (Babb et al, 2002; Bruce, 2012; Cotroneo et al, 2013; Silveri et al, 2008). Citicoline is a compound that consists of cytidine and choline.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Results from this study are consistent with prior research that suggests citicoline may play a role in increasing attention and alertness (Babb et al, 2002; Bruce, 2012; Cotroneo et al, 2013; Silveri et al, 2008). Citicoline is a compound that consists of cytidine and choline.…”
Section: Discussionsupporting
confidence: 89%
“…Citicoline is a compound that consists of cytidine and choline. It has been shown to activate the biosynthesis of phospholipids (PDE) in neuronal membranes (Babb et al, 2002). Since PDE has been shown to decrease with age and be associated with cognitive memory loss, increase in this substance may improve overall cognitive skills.…”
Section: Discussionmentioning
confidence: 99%
“…Citicoline has also been shown to improve cognition in early-onset patients with Alzheimer’s disease (46) and improved performance on some neuropsychological and cognitive tests such as the Mini Mental State Examination (47) in patients with cognitive decline (48). Furthermore, through its effects on phospholipid synthesis, citicoline has been associated with improved memory performance and verbal learning in humans (49). Finally, impulsive behavior and poor decision-making are common in addictions (50), and citicoline-facilitated improvements in cognition may contribute to decreased rates of relapse in addictive disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Babb and colleagues applied proton magnetic resonance spectroscopy (MRS) to measure in-vivo brain chemistry and found that a single oral dose of CDP-choline resulted in increased plasma choline in older (mean age 59 years) and younger (mean age 25) participants three hours after supplementation [7]. These investigators subsequently [8] applied phosphorous MRS to measure changes in brain chemistry in healthy older adults following 6 weeks of 500 mg citicoline supplementation. The study findings showed an increase in brain phosphodiesters that correlated with memory improvement as measured by the California Verbal Learning Test [8].…”
Section: Introductionmentioning
confidence: 99%
“…These investigators subsequently [8] applied phosphorous MRS to measure changes in brain chemistry in healthy older adults following 6 weeks of 500 mg citicoline supplementation. The study findings showed an increase in brain phosphodiesters that correlated with memory improvement as measured by the California Verbal Learning Test [8]. To further examine the potential effects of citicoline supplementation on brain metabolism, Silveri and colleagues used phosphorrus MRS [9] to measure brain metabolites in healthy adults 40 -60 years old who received citicoline supplementation for six weeks at doses of either 500 or 2000 mg/day.…”
Section: Introductionmentioning
confidence: 99%